THE X-RAY DIFFRACTION ANALYSES ON THE MECHANICAL ALLOYING OF THE Mg2Ni FORMATION - Hadi Suwarno; Andon Insani; Wisnu Ari Adi (Jurnal Teknologi Bahan Nuklir, 2007)
Hadi Suwarno*, Andon Insani**, Wisnu Ari Adi** * Centre for Nuclear Fuel Technology - BATAN ** Centre for Nuclear Industry Materials - BATAN Kawasan PUSPIPTEK, Tangerang 15314 ABSTRACT THE X-RAY DIFFRACTION ANALYSES ON THE MECHANICAL ALLOYING OF THE Mg2Ni FORMATION. The synthesis and characterization of Mg2Ni compound by using mechanical alloying technique have been performed. The material is milled under the varied milling time of 20, 25, 30, 35 and 40 hours. The result of measurements by using X-ray diffractometer showed that the refinement results on X-ray diffraction pattern appear to be very good fitting between calculation and observation. It is shown that the specimens consist of three phases, namely Mg2Ni, MgO and MgNi2. For milling time between 20 hours to 25 hours, the mass fraction of the Mg2Ni phase increases from 42.19% to 51.03%. Continuous milling of the specimen up to 40 hours will reduce the Mg2Ni mass fraction to 11.86%, probably due to the presence of oxygen, and consequently will increase the mass fraction of MgNi2 compound. It is concluded that the milling time will influence the formation of Mg2Ni phase. At this research, 25 hours milling time is the best time to obtain the highest formation of Mg2Ni compound. Microstructure analyses of the specimens indicate that milling time of 30 hours is the minimum time required to reduce the particle sizes of the Mg-Ni mixed specimen from 3,5 ~10 tm into nanosize particles. It starts to agglomerate after 40 hours of milling due to the growth of magnetic properties of the powders and the change of crystal orientations into amorphous state. FREE TERMS: High energy ball milling, Crystal structure ABSTRAK ANALISIS DIFRAKSI SINAR-X TERHADAP PEMADUAN MEKANIK PADA PEMBENTUKAN Mg2Ni. Sintesa dan karakterisasi logam paduan Mg2Ni yang dibuat dengan teknik pemaduan mekanik telah dilakukan. Bahan paduan di-milling dengan waktu milling bervariasi yakni 20, 25, 30, 35 dan 40 jam. Hasil pengukuran dengan menggunakan difraktometer sinar-X menunjukkan bahwa hasil pengolahan data atas hasil cacah difraktometer sinar-X sangat sesuai dengan hasil observasi. Hasil olahan menunjukkan bahwa spesimen terdiri dari tiga fasa, yaitu Mg2Ni, MgO dan MgNi2. Untuk waktu milling antara 20 dan 25 jam, fraksi massa fasa Mg2Ni bertambah dari 42,19% menjadi 51,03%. Milling lanjutan hingga 40 jam akan mereduksi fraksi massa fasa Mg2Ni menjadi 11,86%. Hal ini mungkin disebabkan adanya oksigen di dalam mesin milling, dan sebagai konsekuensinya akan menambah fraksi massa fasa MgNi2. Disimpulkan bahwa waktu milling mempengaruhi pembentukan senyawa Mg2Ni. Pada penelitian ini, waktu milling selama 25 jam adalah waktu terbaik untuk pembentukan fasa senyawa Mg2Ni. Analisa mikrostruktur atas spesimen menunjukkan bahwa waktu milling 30 jam adalah waktu minimum yang diperlukan untuk mereduksi ukuran partikel dari 3,5~10 tm menjadi partikel ukuran nano. Setelah milling selama 40 jam spesimen mulai menggumpal yang disebabkan oleh tumbuhnya sifat magnet serbuk dan terjadinya perubahan orientasi kristal menjadi amorf.KATA KUNCI: High energy ball milling, Struktur kristal